Legal Society Service of Pro-Bono on Migrant in Morocco in Law Perspective - Muhammad Amine El Khalfi (LAW FACULTY UNISSULA, 2021)
Morocco is a constitutional, democratic and social monarchy. The King is the Supreme Representative of the Nation and the Symbol of the unity thereof. He is the guarantor of the perpetuation and the continuity of the State. As Defender of the Faith, he ensures the respect for the Constitution. He is the Protector of the rights and liberties of the citizens, social groups and organizations. System Barriers to Pro Bono work result from the social environment of the judiciary and, more specifically, from the current practice of law in Morocco. The population generally has a low regard for the legal and judicial sector, and expects corruption in the judiciary. In Morocco, legal information is also not adequately disseminated to the public.[1] In addition, the low literacy rate 52.3% for the total population (39.6% for women, 65.7% for men) renders access to justice all the more difficult. A substantial proportion of the population is therefore vulnerable and may fall prey to unethical behavior. The Bar Association has great difficulty in supervising “homeless” lawyers, who are lawyers with no fixed business address and operate with a cellular telephone from undisclosed premises. Up to 800 of the 3,000 lawyers registered with the Casablanca Bar Association are reportedly “homeless” lawyers, who prey on the uninformed and often maintain frivolous suits in order to collect higher fees.[1] US Department of State, 2004 census <http://www.state.gov/r/pa/ei/bgn/5431.htm accessed on January 10, 2021